Utility of microminipigs for evaluating liver-mediated gene expression in the presence of neutralizing antibody against vector capsid - Watano, Ryota (Gene Ther, 2020)
Adeno-associated virus (AAV) vectors can transduce hepatocytes efficiently in vivo in various animal species, including humans. Few reports, however, have examined the utility of pigs in gene therapy. Pigs are potentially useful in preclinical studies because of their anatomical and physiological similarity to humans. Here, we evaluated the utility of microminipigs for liver-targeted gene therapy. These pigs were intravenously inoculated with an AAV8 vector encoding the luciferase gene, and gene expression was assessed by an in vivo imaging system. Robust transgene expression was observed almost exclusively in the liver, even though the pig showed a low-titer of neutralizing antibody (NAb) against the AAV8 capsid. We assessed the action of NAbs against AAV, which interfere with AAV vector-mediated gene transfer by intravascular delivery. When a standard dose of vector was administered intravenously, transgene expression was observed in both NAb-negative and low-titer (14×)-positive subjects, whereas gene expression was not observed in animals with higher titers (56×). These results are compatible with our previous observations using nonhuman primates, indicating that pigs are useful in gene therapy experiments, and that the role of low-titer NAb in intravenous administration of the AAV vector shows similarities across species.